Comparative efficacy and acceptability of antimanic drugs in acute mania: a multiple-treatments meta-analysis. - Cipriani, A; Barbui, C; Salanti, G; Rendell, J; Brown, R; Stockton, S; Purgato, M; Spineli, L; Goodwin, G; Geddes, J (2011)
BACKGROUND: Conventional meta-analyses have shown inconsistent results for efficacy of pharmacological treatments for acute mania. We did a multiple-treatments meta-analysis, which accounted for both direct and indirect comparisons, to assess the effects of all antimanic drugs. METHODS: We systematically reviewed 68 randomised controlled trials (16,073 participants) from Jan 1, 1980, to Nov 25, 2010, which compared any of the following pharmacological drugs at therapeutic dose range for the treatment of acute mania in adults: aripiprazole, asenapine, carbamazepine, valproate, gabapentin, haloperidol, lamotrigine, lithium, olanzapine, quetiapine, risperidone, topiramate, and ziprasidone. The main outcomes were the mean change on mania rating scales and the number of patients who dropped out of the allocated treatment at 3 weeks. Analysis was done by intention to treat. FINDINGS: Haloperidol (standardised mean difference [SMD] -0·56 [95% CI -0·69 to -0·43]), risperidone (-0·50 [-0·63 to -0·38), olanzapine (-0·43 [-0·54 to -0·32], lithium (-0·37 [-0·63 to -0·11]), quetiapine (-0·37 [-0·51 to -0·23]), aripiprazole (-0·37 [-0·51 to -0·23]), carbamazepine (-0·36 [-0·60 to -0·11], asenapine (-0·30 [-0·53 to -0·07]), valproate (-0·20 [-0·37 to -0·04]), and ziprasidone (-0·20 [-0·37 to -0·03]) were significantly more effective than placebo, whereas gabapentin, lamotrigine, and topiramate were not. Haloperidol had the highest number of significant differences and was significantly more effective than lithium (SMD -0·19 [95% CI -0·36 to -0·01]), quetiapine (-0·19 [-0·37 to 0·01]), aripiprazole (-0·19 [-0·36 to -0·02]), carbamazepine (-0·20 [-0·36 to -0·01]), asenapine (-0·26 [-0·52 to 0·01]), valproate (-0·36 [-0·56 to -0·15]), ziprasidone -0·36 [-0·56 to -0·15]), lamotrigine (-0·48 [-0·77 to -0·19]), topiramate (-0·63 [-0·84 to -0·43]), and gabapentin (-0·88 [-1·40 to -0·36]). Risperidone and olanzapine had a very similar profile of comparative efficacy, being more effective than valproate, ziprasidone, lamotrigine, topiramate, and gabapentin. Olanzapine, risperidone, and quetiapine led to significantly fewer discontinuations than did lithium, lamotrigine, placebo, topiramate, and gabapentin. INTERPRETATION: Overall, antipsychotic drugs were significantly more effective than mood stabilisers. Risperidone, olanzapine, and haloperidol should be considered as among the best of the available options for the treatment of manic episodes. These results should be considered in the development of clinical practice guidelines. FUNDING: None.